Issues and practices in deciding competency : a discussion paper - Kelly, David J.; Bell, E. J. (Erica Jane), 1962-; Queensland. Board of Senior Secondary School Studies (Brisbane : Queensland Board of Secondary School Studies, 2000)
A research project that investigates issues related to competency-based assessment of vocational education and training (VET), especially in regard to teachers' perceptions of competence.
Includes bibliography.
Also available in an electronic version via the Internet at: http://www.qbssss.edu.au/statisticsandpublications/publications/files/IssuesAndPractices.pdf
Electronic version selected for archiving
Keywords: Competency based education -- Queensland